Hot topics in nutrition research in Ireland. Issue 2 (June 2016) - Nugent, A. P.
Abstract: This article provides a flavour of some of the nutrition‐related research underway in Ireland at present. Specific areas range from biomarker discovery and personalised nutrition to assessments of food, nutrient and food chemical intake using data collected as part of national food surveys. Other areas include the influence of genetics, diet and lifestyle on diet and health outcomes, targeted programmes to assist lifestyle change in 'at risk' groups, such as those at risk of cardiovascular disease. Irish researchers are also collaborating with the food industry to identify and characterise functional foods and bioactives, which can be commercialised. Much of this research feeds into European Union‐wide ventures ranging from Joint Programme Initiatives to the activities of the European Food Safety Authority.